TEMPERATURE COOLING EFECT MODEL OF GREEN OPEN SPACE CASE STUDY DKI JAKARTA - Ilman Rasjiddin, Aude
This research proves that green open space can reduce the temperature in the surrounding area within a certain range. The cooling effect model is created based on the problem of high temperatures which can affect various aspects of human life (Wiryawan 1992, Klemm 2014, Tawatstupa et al. 2010, Akbari et al. 2001, and Mohajerani et al. 2017). Bowler (2010) has concluded that green open space is effective in reducing ambient temperature. DKI Jakarta is urban area which has a temperature that tends to be higher than the surrounding area because of the urban heat island mechanism. On the prevailing guidelines about green open space there is no elaboratation about micro-climate regulation effect or temperature reduction. On the other hand there are no studies on the effects of cooling in DKI Jakarta. Thus, what needs to be done is to formulate an actual model for reducing urban temperatures based on the characteristics of green open space. The variables of this study consist of the dependent variable, namely air temperature, thermal comfort, cooling effect’s range. Meanwhile the independent variables consist of the area of green space, green area coefficient and the proportion of tree cover. The intensity of the cooling effect is seen in two dimensions, namely the intensity of the air temperature and the comfort temperature. In the formulation of macro concepts, the independent variables related to the amount of vegetation can influence the intensity and extent of the cooling effect (Aram et al. 2019). Temperature forming factors other than green open space characteristic in this study seen as given variable. This study mostly uses geographic information systems and remote sensing with Landsat OLI / 8 data analysis. Temperature and comfort temperature are obtained by field survey using Kestrel 5000. Meanwhile, model tests are carried out by multiple regression. The extent of cooling effects from all samples ranged from 0.0094 Ha on 0.109 Ha green open space’s space to 85.048 Ha on 64.867 Ha green open space’s space. The resulting cooling effect extent model is D = 15,205 + 1,032 L. From the model it can be said that the amount of vegetation that affects the extent of the cooling effect is the area of green open space. The average intensity of the greatest cooling effect was found in Monas’ green open space sample with the number ???????????? 20C and ???????????????? 3,9oC. The average ???????????? of the four samples was 1,4oC and ???????????????? was 3,1oC. The resulting cooling effect intensity model is ???????????? = 2,169 KDH-0.5. This meansiv that the amount of vegetation that affects the intensity of the cooling effect is the coefficient of the green open space area. This study confirms that green open space only decreases temperature in the surrounding area, so it cannot be said that green open space decreases overall urban temperature. As conclusion, green open space lowers the temperature in the surrounding area, not lowering the temperature of DKI Jakarta. Green open space has the function of regulating the microclimate, not affecting the macroclimate